Arthroscopic-assisted Distal Radius Fracture Fixation for Dorsoulnar Corner Fragments Using a Locked, Hooked Kirschner-Wire Technique - Ross, Mark; White, Matthew J.; Smith, Nicholas (Journal of Wrist Surgery, 2023)
Background Distal radius fractures with dorso-ulnar corner fragments (DUC) pose a surgical challenge due to limited visualization and the risk of hardware prominence. Traditional approaches often result in inadequate reduction and fixation, leading to suboptimal clinical outcomes.Description of Technique In this study, we introduce an arthroscopic-assisted approach for the fixation of distal radius fractures with DUC fragments. The technique utilizes locked, hooked K-wires to provide a low-profile dorsal capturing mechanism. We outline the step-by-step procedure, which includes pre-operative planning, volar plate application, and arthroscopic reduction of DUC fragments.Materials and Methods We applied this technique to a 60-year-old female patient with an unstable intra-articular distal radius fracture and a DUC fragment. Closed reduction was initially attempted, followed by arthroscopic-assisted reduction and internal fixation using the locked, hooked K-wire technique.Results Our technique has demonstrated its ability to withstand early movement rehabilitation protocols without fixation loss, enabling early mobilization. A custom thermoplastic splint was worn for 6 weeks, with favorable supination/pronation and wrist flexion/extension outcomes at clinical review.Conclusions Arthroscopic-assisted fixation with locked, hooked K-wires offers a reliable solution for accurately reducing challenging DUC fragments in distal radius fractures. This approach complements standard distal radius fixation systems, providing a low-profile dorsal capturing mechanism and addressing the issue of hardware prominence, ultimately improving clinical outcomes.
Keywords: wrist; radius; fracture; arthroscopic; dorsoulnar corner